Enantioselective Difunctionalization of Alkenes by a Palladium‐Catalyzed Heck/Sonogashira Sequence. (27th December 2019) - Zhou, Lujia; Li, Sanliang; Xu, Bing; Ji, Danting; Wu, Lizuo; Liu, Yu; Zhang, Zhan‐Ming; Zhang, Junliang
Abstract: Sonogashira‐type cross‐couplings are one of the most significant alkynylations in organic chemistry. One of the first palladium‐catalyzed intramolecular Heck/Sonogashira reactions of alkenes with terminal alkynes is now reported. With this method, a variety of uniquely substituted chiral benzene‐fused heterocycles bearing a propargyl‐substituted all‐carbon quaternary stereocenter were obtained in a straightforward, high‐yielding, and highly stereoselective manner under mild conditions. Salient features of this process include the use of readily available substrates, high selectivities, a broad substrate scope as well as versatile product functionalizations. Abstract : Eine Palladium‐katalysierte Arylalkinylierung von Alkenen durch eine Heck/Sonogashira‐Sequenz ermöglicht die effiziente Synthese chiraler benzanellierter Heterocyclen mit einem propargylischen quartären Stereozentrum. Diese Reaktion zeichnet sich durch leicht zugängliche Substrate, hohe Selektivitäten und eine große Substratbreite aus.